A class of COPI cargo receptors regulates processing of transmembrane proteins by reinforcing their Golgi retention - Jinghu Gao; Chengge Cong; Yanfang Wu; Yun Xiang; Bing Yan; Qinyu Jia; Zhong-Ping Yao; Yusong Guo; Junjie Hu (Proceedings of the National Academy of Sciences, 2026)
Many transmembrane (TM) signaling receptors undergo essential posttranslational modification in the Golgi prior to their delivery to the plasma membrane (PM). Whether and how the passage and accompanied modification of these proteins across the Golgi is controlled remains unclear. Here, we show that leptin receptor overlapping transcript (LEPROT) and LEPROT-like 1 (LEPROTL1) regulate TM receptor activation by securing their sufficient Golgi retention. LEPROTs localize to cis and medial Golgi in a coat protein complex I (COPI)-dependent manner. LEPROTs interact directly with COPI coats and simultaneously engage a variety of integral membrane proteins with relatively long TM domains at acidic pH. Deletion of LEPROTs in cells causes expedited release of TM receptors transiting through the Golgi. Loss of LEPROTs dysregulates receptor signaling activity, including that of epidermal growth factor receptor (EGFR) and transferrin receptor (TFRC), due to defective modification. Collectively, LEPROTs serve as a class of COPI cargo receptors for TM receptors, ensuring adequate preparation, which is vital for subsequent action on the PM.